Faktor-faktor yang Berhubungan dengan Kecemasan Wanita dalam Menghadapi Menopause di Puskesmas Melur Pekanbaru Tahun 201 - Novita Lusiana (STIKes Hang Tuah Pekanbaru, 2014)
The phase-menopause women, many of them experience clinical and physiological tendency which bother them in daily activates, it also make their life quality worse, inconfidence and make them disquietude. In strength of the data that taken from Department of Health Pekanbaru known that amount number of the women most with 45 to 59 years old, they are in Melur Health Center as many as 678 patients. The purpose of this research is to know the factors which related in disquietude of women in facing menopause in Melur Health Center Pekanbaru 2014. This research type is analytic quantitative with cross sectional design. The research conducted at 11 to 13 April 2014 in Melur Health Center. The populations in this research are all women with 45-59 years old and the sample amount 104 people with taking-sample as propulsivesampling. On the strength of universal analytic known the result that most of the women feel disquiets as many as 56 women (53,8%), lack of knowledge as many as 59 women (56,7%), physically changing as many as 53women (51,0%) and not getting family support as many as 53women (51,0%). And the result of bivariate analytic known that there are relation between knowledge with disquiets Pvalue= 0,008 ≤0,05, there are relationship between physical change with anxiety Pvalue = 0,000 ≤ 0,05, there are relation between family with disquiets Pvalue= 0,002 ≤0,05, women in facing menopause in Melur health center Pekanbaru. To be expected that from Health center’s side can give improving education especially for menopause women facing physically changing in menopause, in order that the information are able to increase women’s knowledge so that women can accept the condition of themselves that they are already been menopause and the women not to be disquiets